New realities in foreign affairs: Diplomacy in the 21st century - Volker Stanzel (Stiftung Wissenschaft und Politik (SWP), 2018)
Modern diplomacy is currently experiencing fundamental changes at an unprecedented rate, which affect the very character of diplomacy as we know it. These changes also affect aspects of domestic and international politics that were once of no great concern to diplomacy. Technical developments, mainly digitization, affect how the work of the diplomat is understood; the number of domestic and international actors whose activity implicates (or is a form of) diplomacy is increasing; the public is more sensitive to foreign policy issues and seeks to influence diplomacy through social media and other platforms; the way exchange between states, as well as the interchange between government and other domestic actors, progresses is influencing diplomacy's ability to act legitimately and effectively; and finally, diplomats themselves do not necessarily need the same attributes as they previously did. These trends, reflecting general societal developments, need to be absorbed by diplomacy as part of state governance.
Keywords: 320